Service Recovery in the Hotel Industry: A Narrative Review - Maryness Patrick; Farida Indriani (Universitas Pendidikan Ganesha, 2026)
This narrative review examines service recovery in the hotel industry from an organizational and operational perspective. Although service recovery has been widely studied, prior research predominantly emphasized customer evaluations, offering limited insight into the internal structures and managerial systems that shape recovery practices. To address this gap, this study synthesizes literature to explain how hotels design, implement, and institutionalize recovery mechanisms as part of their organizational capability. A structured narrative review methodology was employed, drawing on 50 peer-reviewed articles published between 2015 and 2026 and retrieved from Scopus using predefined keywords and screening criteria. The analysis indicates three interconnected aspects of recovery, namely, distributive (including compensation policies and empowerment), procedural (related to complaint-handling systems and workflow design), and interactional (employee communication, empathy, and competence). Findings indicate that the success of recovery processes depends on how much these dimensions are aligned in the formal governance systems, technological systems, and dominant service cultures. Therefore, service recovery is not a frontline action but a system of equity embedded within the network of hotel operations. The review concludes that internal recovery architecture fortification is an effective tool to increase the effectiveness of restoring trust, customer retention, and long-term service resilience in competitive hospitality environments. Practical implications from this study include the need to empower frontline staff, invest in continuous training, and integrate technology to support efficient recovery processes. Additionally, the review identified opportunities for future research, particularly mixed-method studies that compare customer and employee perspectives within evolving hospitality environments.